AI based Mental Health Assisted Chatbot System - Prathaban, Banu Priya; Subash, R.; A, Ashwini; G, Lakshmi (2024 International Conference on Power, Energy, Control and Transmission Systems (ICPECTS), 2024)
The rise of mental health issues globally has necessitated innovative solutions to enhance access to support and resources. In response, this study presents a Mental Health Assisted Chatbot System powered by machine learning algorithms. Leveraging natural language processing (NLP) techniques and sentiment analysis, the chatbot engages users in empathetic conversations, offering personalized support, psycho education, and therapeutic interventions. Through continuous monitoring and analysis of user inputs, the system detects patterns, tracks mood fluctuations, and provides proactive interventions when necessary. While promising, the deployment of such systems raises important considerations regarding privacy, data security, and ethical guidelines. By addressing these challenges, mental health assistant chatbots have the potential to significantly augment mental health care delivery and empower individuals to manage their well-being effectively.